Lack of a relationship between serum ferritin levels and coronary atherosclerosis evaluated by coronary arteriography - Manfroi,W.C. (1999)
Many clinical and epidemiological studies have demonstrated the relationship between serum ferritin and ischemic heart disease. In the present study we evaluated the relationship between coronary heart disease (CHD) and serum ferritin levels in patients submitted to coronary arteriography. We evaluated 307 patients (210 (68.7%) males; median age: 60 years) who were submitted to coronary angiography, measurement of serum ferritin and identification of clinical events of ischemic heart disease. Serum ferritin is reported as quartiles. Ninety-six patients (31.27%) had normal coronary angiography (group 1) and 211 (68.73%) had coronary heart disease (group 2). Of the patients with CHD, 61 (28.9%) had serum ferritin levels higher than 194 ng/ml (4th quartile), as opposed to only 14 (14.58%) of those without CHD (P = 0.0067). In the 2nd quartile, 39 patients (18.48%) had CHD, while 35 patients (36.46%) had normal coronary arteries (P = 0.00064). Multivariate analysis of the data showed that the difference between groups was not statistically significant (P = 0.33). We conclude that there is no independent relationship between coronary heart disease and increased levels of serum ferritin.